南极中山站电离层的极区特征 - 沈长寿; 资民筠; 王劲松; 刘顺林; 徐寄遥 (地球物理学报, 2005)
本文利用1996年的电离层数字测高仪DPS-4所测的f0F2、f0E以及从美国NOAA和DMSP卫星观测估算的半球功率指数和午夜极光区赤道侧边界纬度等资料,考察中山站电离层的极区特征.结果表明,在太阳和地磁宁静环境下,冬季极夜磁正午中山站处于极隙区中心时,电离层内的电离密度达全天的最大值;上、下午各有数小时间隔位于极光带内时,高能粒子的电离作用也很重要;夜间进入极盖区后,电子密度则很低.夏季极昼时,太阳EUV辐射的电离效应使电离层电离密度比冬季值大许多,而且,日变化的最大值时间也提前了1～2h.强磁扰时,极隙区和极光带均向低纬侧移动;中山站上空的电子密度会大幅度下降.在中等扰动环境下情况更加复杂:磁正午前后极隙区内软粒子沉降的电离强度有所减小,而上、下午极光区内的高能粒子电离则有较大增加. We investigate the features of the polar ionosphere over the Zhongshan station in Antarctic using the data of the ionospheric critical frequencies, f(o)F(2) and f(o)E, observed by a Digisonde Portable Sounder( DPS-4) at Zhongshan station of Antarctica in 1996, the hemispheric power index and the midnight equatorward boundary of the aurora estimated by the observation of American NOAA and DMSP satellites. The results show that under a quiet environment of the solar activity and geomagnetic variation at the winter polar night, when the station lies in the center of the polar cleft at magnetic noon, the ionization density of the ionosphere attained to a maximum of the diurnal variation. During several hours before noon and afternoon, the ionized effect of the auroral energy particles is also important. At night the electron density is very low when the station situates at the polar cap area. During the summer polar daylight, the ionized effect of the solar EUV radiation makes the ionospheric electron density much larger and the peak time of the diurnal variation of f(o)F(2) 1-2 hr earlier than that in winter. During a strong geomagnetic disturbance, the locations of both the cleft and aurora move to lower latitudes, and the ionospheric electron density over the Zhongshan station decreases significantly. For a moderate disturbed situation, things become more complex: The strength of ionization caused by soft particles in the cleft around the magnetic noon decreases somewhat, while ionization caused by higher energy particles in the aurora area increases a lot before noon and afternoon. 国家自然科学基金; 国家重点基础研究发展计划(973计划) SCI(E) 中文核心期刊要目总览(PKU) 中国科技核心期刊(ISTIC) 中国科学引文数据库(CSCD) 5 1 1-6 48